Exploring the role of language knowledge and background knowledge in reading comprehension of specific-purpose tests in higher education - Hasan Tarlani-Aliabadi; Khalil Tazik; Zeinab Azizi (Language Testing in Asia, 2022)
Abstract Though the empirical findings of the past studies in the literature have offered strong support to the significant role of language knowledge and background knowledge in reading comprehension, this issue has not been explored with regard to specific purposes tests in the Iranian higher education context. Therefore, this study aimed at exploring the interaction effects between language knowledge and background knowledge among Iranian university students majoring in economics. For this purpose, a total of 90 students including male students (n = 35) and female students (n = 55) majoring in economics were selected through a convenience sampling method. Having been divided into three proficiency levels, they took three high-stakes reading tests constructed by the National Organization of Educational Testing in Iran for Economics candidates. Based on three criteria, including sentences with passive, Flesch Readability Index, and sentences with participles as attributes, the three texts were ranked in order of easy to difficult (text 1, text 2, and text 3). Afterward, 15 participants participated in semi-structured interviews to express their experiences with the reading tests. The results indicated that background knowledge had marked effects on the performances of the participants across the three reading texts. However, in the more specific reading text (text 3), neither general language knowledge nor general background knowledge were strong indicators. Additionally, the results of the semi-structured interviews with the participants revealed they lacked the required language and content knowledge to perform well on the reading text 3. In light of the findings, a range of implications is proposed for pertinent stakeholders.